Bear is a bear - Stutzman, Jonathan (Balzer + Bray, an imprint of HarperCollins Publishers, 2021)
"Bear is . . . a new friend, a fellow mischief-maker, a protector, and a dreamer. Through all the many ups and downs of a little girl's childhood, Bear is there to provide love and support. Until it is time to say goodbye . . . and hello again."--